The precision of the IACT mechanical mounts of the TAIGA observatory - Borodin, A.; Grinyuk, A.; Pan, A.; Sagan, Y.; Tkachev, L.; Zhurov, D.; Astapov, I.; Bezyazeekov, P.; Brueckner, M.; Budnev, N.; Chiavassa, A.; Dyachok, A.; et al. (Scuola Internazionale Superiore di Studi Avanzati, 2023)
The TAIGA (Tunka Advanced Instrument for cosmic ray physics and Gamma Astronomy) observatory is located in the Tunka valley (~50 km west from the southern shore of Lake Baikal) at an altitude of 675m a.s.l. The TAIGA observatory aims to address gamma-ray astronomy at energies from a few TeV to several PeV and CR physics from 100 TeV to several EeV. Its main feature is the complementary, hybrid approach to distinguish CR events from those of gamma rays. Currently TAIGA consists of ~80 wide-angle air Cherenkov detectors (HiSCORE stations), three ~4m diameter IACTs and several hundred surface and underground muon detectors, grouped in three jointly operating arrays. The exceptional feature of the TAIGA IACT array is it’s topology that allows one to aim for the optimal cost/performance by scanning the optimal inter-telescope distances from 300m up to 600m. The IACTs have alt-azimuth type mounts and 576-pixel imaging cameras in the foci, covering 9.6° aperture in the sky. The segmented reflectors of ~10m² area follow the Davis-Cotton design. The largest diameter of the hexagonal shape reflector is 4.3m and the focal length is 4.75m. The rigid telescope mount provides a maximum displacement of EAS image below 2mm (i.e. ≤ 0.024°) in the photodetector plane. The main parameters of IACTs are of a crucial importance for their efficient operation and is presented.